Aplikasi penggajian guru dan karyawan Madrasah Tsanawiyah Nurul Khoiroh berbasis web - Jannah, Faizatul; Muhasshanah, Muhasshanah; Baijuri, Achmad (Universitas Merdeka Malang, 2024)
Payroll can be defined as a form of service system used to make salary payments every month. With a payroll system, the process from start to finish when salaries are paid can run according to what each employee expects. At MTS Nurul Khoiroh, the current payroll system has several obstacles, where the teacher payroll process is still done manually. Payroll data is still calculated and recorded using the Microsoft Excel program and is not in the form of a database, so it is susceptible to loss and errors in data recapitulation at the end of the month. Based on these problems, an application will be created to handle the processing of salary calculation data which is the right of teachers and employees, starting from the process of calculating the basic salary to calculating allowances. The application was built using the waterfall method and with the PHP programming language. With this system, it is hoped that it will make it easier for school treasurers to manage data while also helping to increase the efficiency of the payroll process so that it becomes faster and more accurate.